Strategi Membangun Destinasi Ekowisata di Kawasan Subak Sungsang Desa Tibubiu Kecamatan Kerambitan Kabupaten Tabanan - UTAMI, DEWA AYU PUTU ADI LISTYA; ASTITI, NI WAYAN SRI; PARINING, NYOMAN (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Strategy to Build Ecotourism Destinations in Subak Sungsang Area of Tibubiu Village, Kerambitan District, Tabanan Regency Subak Sungsang is located in Tibubiu village, Kerambitan subdistrict, which has the potential to be developed as an ecotourism destination. The research aims to internal and external factors, also formulate general, alternative, and priority strategies. This research using several analyses, such as IFAS, EFAS, IE matrix, SWOT matrix and QSPM analysis. The results showed that strengths and weakness which come from internal factors are ritual activities or religious culture individually continue to run and the absence of managers for tourism in Subak Sungsang. In other hand, the opportunities and threats which come from external factors are concerns from farmers and tourists towards the subak area and the tendency of people who turn to tourism. General strategy is derived from the total IFAS score of 3,00 and the total EFAS score of 2,26 which is located in cell V (hold and maintain). Alternative strategy consists ten alternative strategies. Priority strategies for the development of Subak Sungsang into ecoturism destination are maintaining natural resources, preserving religious rituals and improving the quality of human resources Subak Sungsang. Advice that can be given is implemeting priority strategies. This strategy can be considered to develop Subak Sungsang as ecotourism destination. In the future, deep and further research is expected to examine supporting factors and inhibitory factors.